Gamified online business simulation: enhancing student motivation in entrepreneurship - Musyaffi, Ayatulloh Michael; Oli, Mario Colega; Mentari, Mely; Afriadi, Bambang (Journal of Education and Learning (EduLearn), 2025)
Entrepreneurship education is growing because of innovative technologies such as artificial intelligence (AI)-based business simulation and gamification. However, there are different responses to gamification-based learning. This study aims to identify the factors that influence learning in gamified business simulation using the self-determination theory (SDT) approach. This study uses a quantitative approach with an online survey of 160 university students learning entrepreneurship through an enterprise resource planning (ERP) based business simulation enhanced with AI and gamification elements. Data were analyzed using importance-performance map analysis (IPMA) to evaluate four primary constructs: autonomy, competence, presence, and relatedness. The analysis results show that the presence construct is fundamental and performs well. While relatedness is fundamental, its performance needs to be improved. The autonomy and competence constructs perform adequately but do not require significant changes. The results also emphasize the importance of strengthening the elements of realism and social interaction in gamified business simulations. Developers and educators should improve the presence and relatedness elements to increase student motivation and engagement. Periodic evaluations and adjustments according to student needs are also necessary to ensure the long-term effectiveness of the simulation. This research provides valuable insights for developing more effective technology-based learning methods in supporting entrepreneurship education.